Computer technology as a pedagogical innovation in physical education of schoolchildren - Borysova, Yu.Yu.; Vlasyuk, E.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : determine the status of implementation of computer programs in physical education of students of Dnipropetrovsk region and the need for automated monitoring systems components of the physical condition of schoolchildren. Material : This survey was attended by 21 physical education teacher: teacher-trainers - 19.05%, with the highest category of teachers - 33.3%, with the first - 23.8%, in the second - 19.05%, professionals - 4.8%. Found that 90.5% of employees feel the need to create an automated system for complete monitoring of the physical condition of students grades 1-11 for the introduction of a differentiated approach in physical education of students. Conclusions . The study results give reason to believe it expedient to establish a comprehensive program of monitoring the physical condition of students based on physical development, functional and physical preparedness depending on features weighty growth indicators.